MEROMBAK STRUKTUR, MEMBENTUK KULTUR PEMBARUAN HUKUM KELUARGA DI INDONESIA - Dede Wahyu (STAINU Tasikmalaya, 2022)
Law is a structure in society that can lead to the formation of a culture. The formation of culture is closely related to the legal system existing in society. Similarly, marriage culture that occurs in society is the result of the formation of a legal structure. In Indonesia, the legal structure of marriage is based on the Marriage Act No. 1 year 1974 and Presidential Instruction No. 1 year 1991 on the Compilation of Islamic Law. These two legal products are controlling the pattern of marriage rules in Indonesia. As time goes by, both products require refinement because of the emergence of the existing of various cases. For example, unregistered marriage that is considered by some people to be the legality of affair where it is due to lack of firmness in the mechanism of marriage recording. Responding to this phenomenon, Musdah Mulia, as an academician, tried to formulate Counter Legal Draft of Compilation of Islamic Law as a form of participating in solving community problems which gradually became a negative culture for the nation. Hukum merupakan suatu struktur dalam masyarakat yang dapat mengarah pada pembentukan suatu kebudayaan. Pembentukan budaya sangat erat kaitannya dengan sistem hukum yang ada di masyarakat. Begitu pula budaya perkawinan yang terjadi di masyarakat merupakan hasil dari pembentukan suatu tatanan hukum. Di Indonesia, struktur hukum perkawinan didasarkan pada Undang-Undang Perkawinan Nomor 1 Tahun 1974 dan Instruksi Presiden Nomor 1 Tahun 1991 tentang Kompilasi Hukum Islam. Kedua produk hukum inilah yang mengontrol pola tata tertib perkawinan di Indonesia. Seiring berjalannya waktu, kedua produk tersebut membutuhkan penyempurnaan karena munculnya berbagai kasus yang ada. Misalnya, perkawinan siri yang dianggap sebagian orang sebagai legalitas perselingkuhan karena tidak adanya ketegasan dalam mekanisme pencatatan perkawinan. Menanggapi fenomena tersebut, Musdah Mulia selaku akademisi berupaya merumuskan Counter Legal Draft Rancangan Hukum Islam sebagai bentuk partisipasi dalam menyelesaikan permasalahan masyarakat yang lambat laun menjadi budaya negatif bagi bangsa.